2021
DOI: 10.1371/journal.pone.0246947
|View full text |Cite
|
Sign up to set email alerts
|

A generalized exponential-type estimator for population mean using auxiliary attributes

Abstract: In this paper, we propose a generalized class of exponential type estimators for estimating the finite population mean using two auxiliary attributes under simple random sampling and stratified random sampling. The bias and mean squared error (MSE) of the proposed class of estimators are derived up to first order of approximation. Both empirical study and theoretical comparisons are discussed. Four populations are used to support the theoretical findings. It is observed that the proposed class of estimators pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 17 publications
(19 reference statements)
0
15
0
Order By: Relevance
“…The PRE of proposed estimator is highest in comparison to the existing estimators as well as all the estimators given in Ahmed et al. [8] . It is observed from Figs.…”
Section: Resultsmentioning
confidence: 76%
See 3 more Smart Citations
“…The PRE of proposed estimator is highest in comparison to the existing estimators as well as all the estimators given in Ahmed et al. [8] . It is observed from Figs.…”
Section: Resultsmentioning
confidence: 76%
“…To examine the dominance and applicability of proposed estimator in simple random sampling, we considered four real data sets from agricultural, fishers and education sectors available in Ahmad et al. [8] . A similar kind of population for reference is given as Appendix A .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, (16) proposed combination of exponential and ln functions under two-phase sampling using two auxiliary variables for estimating population mean. (17) suggested two-exponential shrinkage estimator using two stage two phase sampling for estimating population mean of study variable and (18) suggested generalized class of exponential type estimators for estimating the finite population means using two auxiliary attributes under simple random sampling and stratified random sampling. (19) proposed a class of dual to ratio estimator for estimating the finite population mean in presence of missing values in two-phase sampling design and two different sampling designs in two-phase sampling are compared under imputed data.…”
Section: Introductionmentioning
confidence: 99%